Educamp 2024 inculcating soft skills into the next generation of UiTM doctors - Mahfudz, Anis Shafina; Wan Nordin, Nadzratulaiman; Mat Jin, Norazilah; Omar, Noorkardiffa Syawalina; Ahmad, Zatul Akmar; Mohd Ranai, Norashikin (Faculty of Medicine, 2024)
Soft skills are interpersonal skills relating to how one interacts with colleagues, solve problems and manage their work. They include the ability to communicate clearly, work well with others, adaptability and capability to manage their time effectively.